Problematika Kurangnya Keterlibatan Orang Tua Dalam Mendukung Pendidikan Anak Pada SD Negeri Jatiroke 1 - Hendra Hendra (STIKes Ibnu Sina Ajibarang, 2024)
Lack of parental involvement in supporting children's education is one of the main challenges in efforts to improve the quality of education, especially at the elementary school level. This study aims to identify and analyze the factors that cause minimal parental involvement in children's education at SD Negeri Jatiroke 1. The research method used is a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation. The results of the study indicate that low parental participation is caused by several factors, including limited time due to work, low understanding of the importance of involvement in education, and lack of communication between schools and parents. The implications of this lack of involvement are seen in the less than optimal academic and social development of children. Therefore, it is recommended that there be a collaborative program between schools and parents to increase their participation in supporting children's education in a sustainable manner. It is hoped that through this approach, the quality of education at SD Negeri Jatiroke 1 can be improved and children's development needs can be met comprehensively